2010
DOI: 10.1371/journal.ppat.1000784
|View full text |Cite
|
Sign up to set email alerts
|

A Major Role for the Plasmodium falciparum ApiAP2 Protein PfSIP2 in Chromosome End Biology

Abstract: The heterochromatic environment and physical clustering of chromosome ends at the nuclear periphery provide a functional and structural framework for antigenic variation and evolution of subtelomeric virulence gene families in the malaria parasite Plasmodium falciparum. While recent studies assigned important roles for reversible histone modifications, silent information regulator 2 and heterochromatin protein 1 (PfHP1) in epigenetic control of variegated expression, factors involved in the recruitment and org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
206
2
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(216 citation statements)
references
References 86 publications
6
206
2
2
Order By: Relevance
“…Previous studies have individually investigated 11 Plasmodium ApiAP2 genes functioning in sexual, mosquito, and liver stages in other species (12)(13)(14)(15)(16)(17)(18)(19). In particular, a recent study attempted to knock out all of the ApiAP2 genes and succeeded in disrupting 10 genes in P. berghei (9).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have individually investigated 11 Plasmodium ApiAP2 genes functioning in sexual, mosquito, and liver stages in other species (12)(13)(14)(15)(16)(17)(18)(19). In particular, a recent study attempted to knock out all of the ApiAP2 genes and succeeded in disrupting 10 genes in P. berghei (9).…”
Section: Discussionmentioning
confidence: 99%
“…AP2IX-9 binds DNA in a sequence-specific manner, and the AP2IX-9 binding motif is repeated in many bradyzoite promoters where direct binding of this factor to the BAG1 promoter in chromatin was established. ApiAP2 factors have roles in activating developmental gene expression (13)(14)(15)(16), and there is evidence an ApiAP2 factor may assist the silencing of var gene expression in P. falciparum (17). The AP2IX-9 factor is the first ApiAP2 transcriptional repressor to be characterized in the Apicomplexa, and this mechanism begins to explain how the early steps in tachyzoite to bradyzoite development are regulated in Toxoplasma.…”
Section: Discussionmentioning
confidence: 99%
“…In Toxoplasma, 24 ApiAP2 factors are cell cycle regulated in tachyzoites (8), whereas 18 are expressed in a cascading fashion during the P. falciparum intraerythrocytic cycle (12). Relatively few ApiAP2 proteins are characterized; however, stage-specific gene activation (13)(14)(15)(16) as well as chromatin biology and genome maintenance (17) are functions identified so far. Like their plant counterparts, ApiAP2 factors can bind promoter elements of distinct coregulated gene clusters (12) and, therefore, it is likely these proteins will be major regulators of apicomplexan transcription.…”
mentioning
confidence: 99%
“…Within these upstream regulatory regions DNA elements have been identified by deletion analysis of the 5′UTR and EMSA (16,17). It was demonstrated that one of these motifs, SPE2, specifically binds a member of a newly discovered DNA-binding protein family, ApiAP2, which has a role in chromosome end biology (18). Recently, an additional protein-binding DNA element implicated in mutually exclusive locus recognition was identified in 44 of the var 5′ UTRs (17).…”
mentioning
confidence: 99%